PENYERANGAN SULTAN AGUNG TERHADAP VOC DI BATAVIA TAHUN 1628 DAN 1629 - Triwahana; Siswanta (Universitas PGRI Yogyakarta, 2024)
This research aims: to find out: 1) The background to the attack on Sultan Agung; 2) attacks on Batavia in 1628 and 1629; 3) the impact of Sultan Agung enlightenment on the VOC in Batavia. The method used is the historical method. The stages carried out are: 1) heuristics, 2) source criticism, 3) interpretation and 4) historiography. The research results describe that: 1) The background to Sultan Agung attack on Batavia was caused by several things, including Dutch pressure on the economy of the Mataram people. Apart from that, this was due to Dutch interference in the Mataram government. 2) Sultan Agung attack on Batavia was carried out in 1628 and 1629. The attack in 1628 would be led by Tumenggung Baurekso from Kendal, Tumenggung Suro Agul-Agul, Prince Mandurejo and Duke Upasanta. Meanwhile, the attack in 1629 would be led by Prince Juminah, Prince Purbaya, Prince Puger, they would be assisted by Patih Singoranu, Raden Wira Nata Pada, Tumenggung from Madiun and the Duke of Sumenep. The figure in this second attack was very famous in Mataram. The attack failed because the food supply barn was burned. Apart from that, the time of the attack is also known. This means that Mataram is an agricultural country so the attack must be carried out after the harvest season. 3) As a result of Sultan Agung attack, the Dutch suffered a lot of losses in both property and Dutch soldiers. Apart from that, the Dutch suffered a lot of losses, especially in the rice trade which was monopolized by Mataram. As a result of the attacks in 1628 and 1629, Mataram suffered many losses, especially in the economic sector. To overcome this, Mataram established relations with the Portuguese.